Quality control tests of the front-end optical link components for the ATLAS Liquid Argon Calorimeter Phase-1 upgrade. (3rd August 2021) - Deng, B.; Thomas, J.; Zhang, L.; Baker, E.; Barsallo, A.; Bleile, M.L.; Chen, C.; Cohen, I.; Cruda, E.; Fang, J.; Feng, N.; Gong, D.; et al.
Abstract: We present the procedures and results of the quality control tests for the front-end optical link components in the ATLAS Liquid Argon Calorimeter Phase-1 upgrade. The components include a Vertical-Cavity Surface-Emitting Laser (VCSEL) driver ASIC LOCld, custom optical transmitter/transceiver modules MTx/MTRx, and a transmitter ASIC LOCx2. LOCld, MTx, and LOCx2 each contain two channels with the same structure, while MTRx has a transmitter channel and a receiver channel. Each channel is tested at 5.12 Gbps. A total of 5341 LOCld chips, 3275 MTx modules, 797 MTRx modules, and 3198 LOCx2 chips are qualified. The yields are 73.9%, 98.0%, 98.4%, and 61.9% for LOCld, LOCx2, MTx, and MTRx, respectively.